COVID-19 and Rapid Course Adaptations in Saudi Arabia: An Experiential Learning and Recommendations for Online Education - Alatni, Basim Sulaiman; Abubakar, Ismaila Rimi; Iqbal, Saad Arslan (Frontiers in Psychology, 2021)
The COVID-19 Pandemic has severely impacted educational systems around the globe, necessitating rapid modifications to the educational milieu while safeguarding human health and wellbeing. Following the closure of universities in Saudi Arabia, instructors of all theory courses were mandated to switch from face-to-face course delivery to remote teaching and learning. This research examines the challenges and impacts of the COVID-19 Pandemic on the mode of teaching and learning and the numerous adaptations in the pedagogical framework in the Landscape Architecture program at Imam Abdulrahman Bin Faisal University, Saudi Arabia. It also explores the opportunities the transition to online education presents to faculty and students moving forward. The data were collected using an online questionnaire survey and focus group discussions. Data analyses consisted of descriptive statistics and thematic content analysis. The research finds that the sudden transition to online teaching and learning disrupted academic activities and had negatively affected the existing teaching and learning framework. Therefore, the research recommends an adaptable and dynamic teaching framework agile enough to cope with sudden disruptions. It concludes with lessons for future teaching and learning frameworks and amendments for upcoming sessions to deal with similar situations.